SISTEM INFORMASI PENGOLAHAN DATA PERTANIAN BERBASIS WEB DI DESA KARANG DUREN - Resti Sutianingtyas; Guruh Wijaya; Miftahur Rahman (Fakultas Sains dan Teknologi, Universitas Ibrahimy, 2023)
The agricultural sector is one of the employment sectors for most residents of Karang Duren village. In general, the management of agricultural process data at the planting and harvesting stages has not yet implemented information technology, so there are several weaknesses such as inefficient and effective data management. The agricultural process data management application is an application designed for the planting and harvesting stages. With this application you can schedule planting, fertilizing, managing drugs and pests, as well as harvesting. This application is made using the steps of the waterfall model software engineering method. To ensure the suitability of the running of this application is tested using black box testing. This app will help farmers with planting planning, fertilizing, managing pesticides and harvesting. With this planning, each activity can be monitored with a plan that has been prepared to minimize deviations that occur.